Hot-melt extrusion technique: A novel continuous manufacturing method for enteric-coated pellets - Rajeshwari Roychowdhury, Divya Dhatri Kara, Mahalaxmi Rathnanand (Journal of Applied Pharmaceutical Science, 2021)
The technology of hot-melt extrusion (HME) is becoming a progressively appealing way to develop different drug delivery systems. A wide range of pharmaceutical dosage forms and formulations from oral to topical and parenteral can be prepared. The dosage forms formulated using HME technique are composite mixtures of active pharmaceutical agents, active excipients, and other processing aids. HME has many advantages over traditional techniques of pharmaceutical development, such as non-solvent technology, lower processing requirements, uninterrupted activity, and greater possibility of uniform suspension and increased bioavailability. This paper addresses enteric-coated pellet pharmaceutical applications and its process techniques using the HME technology and its applications in pharmaceutical industries for an efficient pathway for a novel drug delivery system.
Keywords: Hot-melt extrusion (HME), enteric-coated pellets, pelletization, twin screw extruder, novel drug delivery system (NDDS).